Preparation method of multi-vacancy core-shell ZnO (at) ZnS heterojunction, product and application of multi-vacancy core-shell ZnO (at) ZnS heterojunction
The preparation of multi-vacous core-shell ZnO@ZnS heterojunctions through the template method solves the problem of insufficient photocatalytic degradation performance in high salinity seawater in the prior art, and achieves efficient degradation of seawater under visible light The effect of pollutants.
Patent Information
- Application Number
- CN202411689712.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing ZnO@ZnS heterojunction and its preparation method are insufficient in high salinity seawater, and the preparation method is complex, which is not conducive to large-scale production.
The multi-vac core-shell ZnO@ZnS heterojunction was prepared by template method. Through the preparation of ZnTMT template, the synthesis of ZnS and the high-temperature calcination of ZnO@ZnS heterojunction, a heterojunction with zinc vacancies, oxygen vacancies and sulfur vacancies were formed. .
It significantly improves the separation efficiency of photogenerated carriers, enhances photocatalytic performance, and can efficiently degrade pollutants in high salinity seawater under visible light irradiation, and is suitable for seawater pollution treatment.
Smart Images

Figure CN119425732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalysis technology, and in particular to a preparation method, product and application of a multi-vacancy core-shell ZnO@ZnS heterojunction. Background Art
[0002] In modern society, the problem of marine pollution is becoming increasingly serious and has become a focus of global attention. Marine pollution not only destroys the balance of the marine ecosystem, but also has serious impacts on human health and economic development. The sources of marine pollution are diverse, including heavy metal pollution (such as mercury, arsenic, cadmium, etc.), plastic pollution, crude oil spills, and organic pollution discharged by agricultural and industrial activities. In particular, with the continuous expansion of marine and aquaculture activities, the problem of antibiotic pollution has become increasingly serious. These pollutants have caused long-term harm to marine life and affected human health through the food chain. Therefore, the development of efficient and environmentally sustainable methods for treating seawater pollution has become an important area of contemporary research.
[0003] ZnS and ZnO are typical II-VI wide bandgap semiconductor materials that can effectively generate photocarriers and exhibit photocatalytic activity under ultraviolet irradiation. These two materials show great application potential in the field of photocatalysis due to their unique electronic structure and optical properties. However, the wide band gaps of ZnO (band gap Eg = 3.2 eV) and ZnS (band gap Eg = 3.6 eV) limit their efficiency in utilizing solar energy because they mainly absorb ultraviolet light and have weak absorption capacity for visible light. In addition, photogenerated carriers are prone to recombination in these materials, which greatly hinders their application in photocatalytic processes.
[0004] To overcome these limitations, researchers have explored combining ZnO and ZnS to form heterojunction structures. Heterojunction structures can lower the photoexcitation threshold and reduce the electron-hole pair recombination rate, thereby improving the photocatalytic efficiency. Both materials have similar metal elements and compatible band structures, which promote effective lattice matching and make it possible to in situ construct an S-type heterojunction between ZnS and ZnO. When preparing catalysts containing ZnO or ZnS, a large number of vacancies are usually formed on the catalyst surface. These vacancies can effectively capture charge carriers reaching the surface, thereby improving the charge separation efficiency. This process helps to form impurity energy bands, broaden the spectral response range, and ultimately improve the activity of the photooxidation or reduction process.
[0005] For example, the prior art CN118002152A, the invention name is a ZnO / ZnS composite material with zinc and oxygen double vacancies, its preparation method and application. The ZnO / ZnS composite material disclosed therein belongs to a hollow spherical structure, which has zinc and oxygen double vacancies and has the performance of photocatalytic decomposition of water to produce hydrogen. The prior art CN106622291A, the invention name is a method for preparing zinc oxide / zinc sulfide nanoheterojunction photocatalyst. The ZnO / ZnS nanoheterojunction photocatalyst disclosed therein also has the performance of photocatalytic decomposition of water to produce hydrogen, and the photocatalytic hydrogen production efficiency is high, but its preparation method is relatively complicated and has limitations for large-scale production. The prior art CN114558592B, the invention name is a ZnO / ZnS nanorod core-shell structure photocatalyst and its preparation method, wherein a rod-shaped core-shell photocatalyst is prepared by combining electrodeposition and spin coating, the preparation method is complicated, the cost is high, and it is not conducive to large-scale production. Furthermore, none of the above-mentioned prior arts have studied the performance under complex environmental conditions, such as high-salinity seawater.
[0006] It can be seen that the above-mentioned existing heterojunction ZnO@ZnS and its preparation method and application still have inconveniences and defects, and are in urgent need of further improvement. How to create a new multi-vacancy core-shell ZnO@ZnS heterojunction preparation method and product and application, so that it can be simply and conveniently prepared by template method with zinc vacancies, oxygen vacancies and sulfur vacancies. The core-shell S-type heterojunction ZnO@ZnS with significantly improved photogenerated carrier separation efficiency, enhanced photocatalytic performance, and effectively degrade pollutants in high-salinity seawater, providing practical application value for seawater pollution treatment. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction, so that a core-shell S-type heterojunction ZnO@ZnS with zinc vacancies, oxygen vacancies and sulfur vacancies can be simply and conveniently prepared, the separation efficiency of photogenerated carriers can be significantly improved, the photocatalytic performance can be enhanced, and the pollutants in high-salinity seawater can be effectively degraded, providing practical application value for seawater pollution treatment, thereby overcoming the shortcomings of the existing ZnO@ZnS heterojunction and its preparation method.
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction, characterized in that it comprises the following steps:
[0009] (1) Preparation of ZnTMT:
[0010] Place the sodium hydroxide aqueous solution in a water bath at 60-80°C, add TMT powder, and continue stirring to form solution A;
[0011] Weigh zinc nitrate hexahydrate and dissolve it in water, stirring continuously to form solution B;
[0012] Slowly add solution A to solution B to form a white solution, stir at room temperature for 24-48 hours to form a metal-coordination polymer ZnTMT precipitate, centrifuge at low speed, wash, and dry at 60-80°C overnight to obtain a metal-coordination polymer ZnTMT powder;
[0013] (2) Preparation of ZnS:
[0014] Weigh ZnTMT powder, add ultrapure water, stir at room temperature for 30-60 minutes, transfer to a reactor, keep at 140-200°C for 12-18 hours, wash the precipitate, and dry at 60-80°C overnight to obtain light yellow ZnS powder;
[0015] (3) Preparation of ZnO@ZnS heterojunction:
[0016] The ZnS powder was weighed and evenly placed in an alumina crucible, and calcined at 300-600° C. in a tube furnace. After the calcination was completed, the powder was naturally cooled to room temperature to obtain a multi-vacancy core-shell ZnO@ZnS heterojunction.
[0017] Further improvement, step (1) is specifically as follows:
[0018] Weigh 0.03-0.05 mol of NaOH and dissolve it in 200-400 mL of ultrapure water, place it in a 60-80°C water bath, and add 0.01-0.03 mol of TMT powder, stirring continuously to form solution A;
[0019] Weigh 0.03-0.05 mol of Zn(NO3)2﹒6H2O and add it to 200-400 mL of ultrapure water. Stir continuously for 30-60 min at room temperature to form solution B.
[0020] Solution A is slowly added to solution B to form a white solution, which is then stirred at room temperature for 24-48 hours to form a metal-coordination polymer ZnTMT precipitate. The precipitate is centrifuged at low speed, washed with ultrapure water, and dried at 60-80°C overnight to obtain a metal-coordination polymer ZnTMT powder.
[0021] Further improvement, step (2) is specifically as follows:
[0022] Weigh 1-3 g of ZnTMT powder, add 50-100 mL of ultrapure water, stir at room temperature for 30-60 min, transfer to a reactor, keep at 140-200 ° C for 12-18 h, wash the precipitate, and dry it at 60-80 ° C overnight to obtain light yellow ZnS powder.
[0023] Further improvement, the calcination time in step (3) is 1-3h.
[0024] As a further improvement, step (3) also includes the step of delivering air into the reaction furnace by an external air pump during the initial stage of calcination to enhance the contact between the reactants and oxygen and optimize the conditions for converting ZnS to ZnO.
[0025] As a further improvement, the flow rate of air delivered to the reaction furnace is 100 mL / min.
[0026] As another improvement of the present invention, the present invention also provides a multi-vacancy core-shell ZnO@ZnS heterojunction prepared by the above-mentioned multi-vacancy core-shell ZnO@ZnS heterojunction preparation method. The multi-vacancy core-shell ZnO@ZnS heterojunction is a spherical structure, with a ZnS core inside and a ZnO shell outside, and the ZnO@ZnS heterojunction has a multi-vacancy structure, and the multi-vacancy structures are zinc vacancies, oxygen vacancies and sulfur vacancies.
[0027] As another improvement of the present invention, the present invention also provides an application of the above-mentioned multi-vacancy core-shell ZnO@ZnS heterojunction in the degradation of organic pollutants in seawater under visible light irradiation.
[0028] The degradation rate of the multi-vacancy core-shell ZnO@ZnS heterojunction in degrading OTC in seawater under visible light irradiation is greater than 50%.
[0029] After adopting such a design, the present invention has at least the following advantages:
[0030] 1. The method for preparing the ZnO@ZnS heterojunction of the present invention is efficient, simple, easy to operate, low-cost, and conducive to large-scale production. The prepared ZnO@ZnS heterojunction has a variety of vacancy defects, including zinc vacancies, oxygen vacancies, and sulfur vacancies. In the photocatalytic reaction process, these vacancies can effectively capture the charge carriers reaching the surface, improve the charge separation efficiency, help to form impurity energy bands, broaden the spectral response range, and ultimately improve the activity of the photooxidation or reduction process, thereby enhancing the photocatalytic activity.
[0031] 2. The present invention simulates the conditions of most salts in seawater by adjusting the types and concentrations of different salts, explores the performance of the ZnO@ZnS heterojunction in degrading high concentrations of OTC under visible light, and carries out photocatalytic degradation in actual seawater, confirming that the ZnO@ZnS heterojunction has excellent photocatalytic degradation performance in simulated or real seawater under visible light irradiation, indicating that the ZnO@ZnS heterojunction can achieve efficient degradation of organic pollutants in seawater without increasing additional energy consumption, and has important environmental and economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0033] Figure 1 It is a flow chart of the method for preparing the ZnO@ZnS heterojunction of the present invention.
[0034] Figure 2 It is a scanning electron microscope (SEM) image of the ZnO@ZnS heterojunction prepared in the present invention.
[0035] Figure 3 It is a transmission electron microscope (TEM) image of the ZnO@ZnS heterojunction prepared in the present invention.
[0036] Figure 4 It is the electron paramagnetic resonance (EPR) spectrum of the ZnO@ZnS heterojunction prepared by the present invention.
[0037] Figure 5 It is the UV-visible absorption spectrum of OTC in Example 4 in a simulated seawater solution containing 3.5 wt % NaCl.
[0038] Figure 6 This is a standard curve of the absorbance of OTC in high salt solution and aqueous solution at a wavelength of 355 nm in Example 4.
[0039] Figure 7 This is a curve diagram showing the dynamic changes in the degradation efficiency of OTC in a simulated seawater solution with different catalysts in Example 4 of the present invention.
[0040] Figure 8 Graph showing the degradation efficiency of OTC by the ZnO@ZnS heterojunction in Examples 5 and 6 of the present invention at different salt concentrations and in Bohai Sea water. DETAILED DESCRIPTION
[0041] The exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0042] Example 1: Preparation of multi-vacancy core-shell ZnO@ZnS heterojunction
[0043] Figure 1 The preparation process of ZnO@ZnS heterojunction is demonstrated, including the preparation of ZnTMT template, synthesis of ZnS and the formation of ZnO@ZnS heterojunction. The specific preparation is:
[0044] 1. Chemical reagents
[0045] Sodium hydroxide: NaOH, Sinopharm Chemical Reagent Co., Ltd.; zinc nitrate: Zn(NO3)2·6H2O, Sinopharm Chemical Reagent Co., Ltd.; thiocyanate: C3H3N3S3, TMT, Shanghai Aladdin Biochemical Technology Co., Ltd. It should be noted that the reagents used in this application are all commercially available chemical reagents.
[0046] 2. Preparation method
[0047] (1) Preparation of ZnTMT template
[0048] Weigh 0.03 mol of NaOH and dissolve it in 200 mL of ultrapure water. Heat the mixture in a 60° C. water bath. Then add 0.01 mol of TMT powder and continue stirring for 30 min to form a uniformly mixed solution A.
[0049] Weigh 0.03 mol of Zn(NO3)2·6H2O and add it to 200 mL of ultrapure water. Stir continuously for 45 min at room temperature to form solution B.
[0050] Solution A was slowly added to solution B to form a white precipitate, which was then stirred at room temperature for 24 h to form a ZnTMT metal-coordination polymer precipitate.
[0051] The precipitate was centrifuged at low speed, collected, washed three times with ultrapure water, and then dried at 60° C. overnight to obtain a metal-coordination polymer ZnTMT white powder.
[0052] (2) Preparation of ZnS
[0053] Weigh 1g of ZnTMT powder, add it to 100mL of ultrapure water, and stir it at room temperature for 30min. Transfer the above solution to a 100mL polytetrafluoroethylene reactor and keep it at 140℃ for 12h. After the reaction is completed, wash the precipitate three times with ultrapure water and dry it at 60℃ overnight to obtain ZnS powder.
[0054] (3) Preparation of ZnO@ZnS heterojunction
[0055] 0.5 g of ZnS powder was weighed and evenly dispersed in an alumina crucible, and calcined at 550° C. in a tube furnace for 2 h. After calcination, it was naturally cooled to room temperature to obtain a multi-vacancy core-shell ZnO@ZnS heterojunction powder.
[0056] Example 2: Preparation of multi-vacancy core-shell ZnO@ZnS heterojunction
[0057] 1. Chemical reagents
[0058] Sodium hydroxide: NaOH, Sinopharm Chemical Reagent Co., Ltd.; zinc nitrate: Zn(NO3)2·6H2O, Sinopharm Chemical Reagent Co., Ltd.; thiocyanate: C3H3N3S3, TMT, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0059] 2. Preparation method
[0060] (1) Preparation of ZnTMT template
[0061] Weigh 0.05 mol of NaOH and dissolve it in 400 mL of ultrapure water. Heat the mixture in a water bath at 80° C., then add 0.03 mol of TMT powder and continue stirring for 30 min to form a uniformly mixed solution A.
[0062] Weigh 0.05 mol of Zn(NO3)2·6H2O and add it to 400 mL of ultrapure water. Stir continuously for 60 min at room temperature to form solution B.
[0063] Solution A was slowly added to solution B to form a white precipitate, which was then stirred at room temperature for 48 h to form a ZnTMT metal-coordination polymer precipitate.
[0064] The precipitate was centrifuged at low speed, collected, washed three times with ultrapure water, and then dried at 80° C. overnight to obtain a metal-coordination polymer ZnTMT white powder.
[0065] (2) Preparation of ZnS
[0066] Weigh 3 g of ZnTMT powder, add it to 100 mL of ultrapure water, and stir it at room temperature for 50 min. Transfer the above solution to a 100 mL polytetrafluoroethylene reactor and keep it at 200 ° C for 18 h. After the reaction is completed, wash the precipitate three times with ultrapure water and dry it at 80 ° C overnight to obtain ZnS powder.
[0067] (3) Preparation of ZnO@ZnS heterojunction
[0068] 1.0 g of ZnS powder was weighed and evenly dispersed in an alumina crucible, and calcined at 600° C. in a tube furnace for 3 h.
[0069] And within 30 min of the initial stage of calcination, air was delivered into the furnace through an external air pump at a flow rate of 100 mL / min to enhance the contact between the reactants and oxygen.
[0070] After the calcination is completed, the mixture is naturally cooled to room temperature to obtain a multi-vacancy core-shell ZnO@ZnS heterojunction powder.
[0071] Example 3 Structural Detection of Multi-Vacancy Core-Shell ZnO@ZnS Heterojunction
[0072] The ZnO@ZnS heterojunction powder obtained in Example 1 was subjected to scanning electron microscopy (SEM), transmission electron microscopy (TEM), and electron paramagnetic resonance (EPR) tests. The results are shown in the attached figure. Figure 2 , 3 、4.
[0073] Figure 2 The scanning electron microscope (SEM) image of the ZnO@ZnS heterojunction is shown, which shows the spherical structure and size of the ZnO@ZnS heterojunction, and the EDS spectrum reveals the distribution of elements such as Zn, S, and O in the heterojunction.
[0074] Figure 3 The transmission electron microscope (TEM) image of the ZnO@ZnS heterojunction is shown. As can be seen from the image, the inner layer is the ZnS core and the outer layer is the ZnO shell. The ZnS core and the ZnO shell in the ZnO@ZnS heterojunction are bonded by chemical bonds.
[0075] Figure 4 The electron paramagnetic resonance (EPR) image of the ZnO@ZnS heterojunction is shown. It can be seen from the image that there are various vacancy defects on the surface of the ZnO@ZnS heterojunction, including zinc vacancies, oxygen vacancies, and sulfur vacancies.
[0076] Example 4: Verification of the photocatalytic degradation activity of ZnO@ZnS heterojunction
[0077] In actual seawater pollutant detection, oxytetracycline is one of the representative antibiotics in the detected antibiotic pollution, and the main reason is that oxytetracycline is common and common in veterinary antibiotics, which usually causes oxytetracycline to be abused. Similarly, there is the same problem in mariculture, and these abused oxytetracyclines are released into the ocean in large quantities along with the discharge of mariculture wastewater, thereby aggravating the antibiotic pollution in the ocean. Therefore, the present embodiment selects oxytetracycline (OTC) as a representative pollutant of marine organic pollutants, and by verifying the degradation rate of OTC in simulated seawater under high salt concentration by ZnO@ZnS heterojunction, it is illustrated that the ZnO@ZnS heterojunction prepared by the present invention has a strong photocatalytic degradation effect, which can provide a reliable basis for degrading seawater organic pollutants under visible light conditions.
[0078] First, determine the optimal test wavelength for OTC
[0079] OTC solutions of different concentrations were prepared, with 3.5wt% NaCl solution as the solvent, to obtain OTC solutions with concentrations of 5, 10, 20, 30, 40, and 50ppm. The spectrum was measured using an ultraviolet spectrophotometer, with the test spectrum range of 200-450nm. The obtained ultraviolet spectrophotometer spectrum is shown in the attached figure. Figure 5 shown.
[0080] from Figure 5 It can be seen that OTC has maximum absorption wavelengths at 275nm and 355nm. Considering that the intermediate products of OTC in the degradation process may affect the absorbance in the ultraviolet region, 355nm was selected as the best test wavelength.
[0081] Secondly, the difference in the absorbance of OTC in high salt water and pure water was investigated.
[0082] In order to exclude the possible effect of high-salt environment on the degradation of the catalyst, this example also compares the absorbance difference of OTC in pure water and in high-salt water. The specific method is:
[0083] Using pure water or 3.5wt% NaCl solution as solvent, we prepared OTC solutions with concentrations of 5, 10, 20, 30, 40, and 50ppm, and tested the absorbance of the prepared solutions at a test wavelength of 355nm, and drew standard curves for OTC solutions with different solvents. The results are shown in the attached figure. Figure 6 shown.
[0084] from Figure 6 It can be seen that at a wavelength of 355nm, the standard curves of the aqueous solution of OTC and the high-salt solution of OTC are basically consistent, with no significant difference. The results show that the OTC in the high-salt solution is evenly dispersed and will not affect the degradation of the catalyst.
[0085] Next, based on the above, the catalytic effect of the ZnO@ZnS heterojunction prepared in this application as a photocatalyst is compared. The specific method is:
[0086] Using 3.5wt% NaCl solution as solvent, a 50ppm OTC solution was prepared and divided into four equal parts. 0.03g of ZnO, ZnS, ZnTMT and ZnO@ZnS were added respectively as different catalysts. Dark adsorption was performed for 30min under dark conditions to allow each catalyst to reach adsorption equilibrium with OTC and eliminate possible adsorption effects in the subsequent photocatalytic degradation process. After the adsorption equilibrium time was reached, the xenon lamp source was turned on to conduct the photocatalytic degradation experiment.
[0087] During the experiment, a 1 mL syringe was used to sample 1 mL of each OTC solution every 30 min. The obtained solution was filtered through a 0.22 μm water filter to obtain a clear OTC solution, and the absorbance was measured by an ultraviolet spectrophotometer at a wavelength of 355 nm. The degradation rate of OTC by different catalysts was calculated, and the results are shown in Table 1 and Appendix. Figure 7 shown.
[0088] Table 1 Degradation rate of OTC by different catalysts
[0089] Different catalysts OTC degradation rate (%) ZnO 50.9 ZnS 8.5 ZnTMT 21.9 ZnO@ZnS 73.6
[0090] From Table 1 and Figure 7 It can be seen that under the same NaCl high-salt environment, the ZnO@ZnS heterojunction has always shown the best photocatalytic degradation effect of OTC in the degradation solution. Moreover, after 240 minutes of illumination, the degradation rate of OTC by the ZnO@ZnS heterojunction reached 73.6%, which is much higher than the degradation rate of ZnTMT, ZnS and ZnO alone, showing the excellent photocatalytic degradation performance of the ZnO@ZnS heterojunction under high-salt conditions.
[0091] Example 5: Photocatalytic degradation experiment of ZnO@ZnS heterojunction at different salt concentrations
[0092] Since seawater contains a variety of salts, in order to verify the photocatalytic degradation effect of the ZnO@ZnS heterojunction under different salt concentrations, the following experiment was conducted in this example.
[0093] Simulated seawater solutions containing 3.5wt% NaCl, 4.46wt% KCl, 2.84wt% MgCl2, 3.32wt% CaCl2, 4.25wt% Na2SO4 and 7.34wt% KBr were prepared respectively, 50mL of each solution was taken, and OTC was added to make the OTC concentration 50ppm.
[0094] Then, 0.03 g of ZnO@ZnS heterojunction was added to each high-salt solution, and dark adsorption was carried out for 30 min in dark conditions. After the adsorption equilibrium time was reached, the xenon lamp source was turned on to carry out a photocatalytic degradation experiment.
[0095] During the experiment, a 1 mL syringe was used to sample 1 mL of each high-salt solution every 30 min. The obtained solution was filtered through a 0.22 μm water filter, and the absorbance of the obtained clear solution was measured by UV spectrophotometer at a wavelength of 355 nm. The degradation rate of OTC by the photocatalyst ZnO@ZnS heterojunction in different high-salt solutions was calculated. The results are shown in Table 2 and Appendix. Figure 8 shown.
[0096] Table 2 Degradation rate of OTC by photocatalyst ZnO@ZnS heterojunction in different high-salt solutions
[0097] Different high salt solutions OTC degradation rate (%) 3.5wt%NaCl 73.6 4.46wt%KCl 73.0 <![CDATA[2.84wt%MgCl2]]> 50.7 <![CDATA[3.32wt%CaCl2]]> 59.4 <![CDATA[4.25wt%Na2SO4]]> 68.7 7.34wt%KBr 70.7
[0098] From Table 2 and Figure 8 It can be seen that the ZnO@ZnS heterojunction can show a significant degradation effect on OTC under different high-salt simulated seawater conditions, and the degradation rate is greater than 50%. It further shows that the ZnO@ZnS heterojunction prepared by the present invention has the application potential of showing excellent photocatalytic degradation performance in seawater environment.
[0099] Example 6: Photocatalytic degradation experiment of ZnO@ZnS heterojunction in actual seawater
[0100] In order to evaluate the photocatalytic performance of ZnO@ZnS heterojunction in an actual seawater environment, this example is as follows:
[0101] Seawater from the Bohai Sea was used as a solvent, and OTC was added to make the OTC concentration 50 ppm.
[0102] Then, 0.03 g of ZnO@ZnS heterojunction was added to the seawater solution. Dark adsorption was performed for 30 min in the dark. After the adsorption equilibrium time was reached, the xenon lamp was turned on to conduct a photocatalytic degradation experiment.
[0103] During the experiment, a 1 mL syringe was used to sample 1 mL of the seawater solution every 30 min. The obtained solution was filtered through a 0.22 μm water filter, and the absorbance of the obtained clear solution was measured by an ultraviolet spectrophotometer at a wavelength of 355 nm. The degradation rate of the photocatalyst ZnO@ZnS heterojunction on OTC in the seawater solution was calculated, and the results are shown in Table 3 and Appendix. Figure 8 shown.
[0104] Table 3 Degradation rate of OTC by photocatalyst ZnO@ZnS heterojunction in seawater solution
[0105] sea water solution OTC degradation rate (%) Bohai Sea water 68.9
[0106] From Table 3 and Figure 8 It can be seen that the degradation efficiency of OTC by the ZnO@ZnS heterojunction under actual seawater conditions can reach 68.9%, which further proves the effectiveness and application potential of the ZnO@ZnS heterojunction in actual seawater pollution treatment. That is, the ZnO@ZnS heterojunction can degrade organic pollutants in seawater under visible light irradiation, providing practical application value for the treatment of organic pollutants in real seawater.
[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Those skilled in the art may make some simple modifications, equivalent changes or modifications using the technical contents disclosed above, which all fall within the protection scope of the present invention.
Claims
1. A method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction, characterized in that: The steps include: (1) Preparation of ZnTMT: Place the sodium hydroxide aqueous solution in a water bath at 60-80°C, add TMT powder, and continue stirring to form solution A; Weigh zinc nitrate hexahydrate and dissolve it in water, stirring continuously to form solution B; Slowly add solution A to solution B to form a white solution, stir at room temperature for 24-48 hours to form a metal-coordination polymer ZnTMT precipitate, centrifuge at low speed, wash, and dry at 60-80°C overnight to obtain a metal-coordination polymer ZnTMT powder; (2) Preparation of ZnS: Weigh ZnTMT powder, add ultrapure water, stir at room temperature for 30-60 minutes, transfer to a reactor, keep at 140-200°C for 12-18 hours, wash the precipitate, and dry at 60-80°C overnight to obtain light yellow ZnS powder; (3) Preparation of ZnO@ZnS heterojunction: The ZnS powder was weighed and evenly placed in an alumina crucible, and calcined at 300-600° C. in a tube furnace. After the calcination was completed, the powder was naturally cooled to room temperature to obtain a multi-vacancy core-shell ZnO@ZnS heterojunction.
2. The method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 1, characterized in that: Step (1) is specifically as follows: Weigh 0.03-0.05 mol of NaOH and dissolve it in 200-400 mL of ultrapure water, place it in a 60-80°C water bath, and add 0.01-0.03 mol of TMT powder, stirring continuously to form solution A; Weigh 0.03-0.05 mol of Zn(NO3)2﹒6H2O and add it to 200-400 mL of ultrapure water. Stir continuously for 30-60 min at room temperature to form solution B. Solution A is slowly added to solution B to form a white solution, which is then stirred at room temperature for 24-48 hours to form a metal-coordination polymer ZnTMT precipitate. The precipitate is centrifuged at low speed, washed with ultrapure water, and dried at 60-80°C overnight to obtain a metal-coordination polymer ZnTMT powder.
3. The method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 1, characterized in that: Step (2) is specifically as follows: Weigh 1-3 g of ZnTMT powder, add 50-100 mL of ultrapure water, stir at room temperature for 30-60 min, transfer to a reactor, keep at 140-200 ° C for 12-18 h, wash the precipitate, and dry it at 60-80 ° C overnight to obtain light yellow ZnS powder.
4. The method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 1, characterized in that: The calcination time in step (3) is 1-3h.
5. The method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 4, characterized in that: Step (3) also includes the step of supplying air into the reaction furnace through an external air pump during the initial stage of calcination.
6. The method for preparing a multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 5, characterized in that: The flow rate of air delivered to the reactor was 100 mL / min.
7. A multi-vacancy core-shell ZnO@ZnS heterojunction, characterized in that: The ZnO@ZnS heterojunction is prepared by the method for preparing the multi-vacancy core-shell ZnO@ZnS heterojunction according to any one of claims 1 to 6.
8. The multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 7, characterized in that: The multi-vacancy core-shell ZnO@ZnS heterojunction is a spherical structure, with a ZnS core inside and a ZnO shell outside, and the ZnO@ZnS heterojunction has a multi-vacancy structure, which includes zinc vacancies, oxygen vacancies and sulfur vacancies.
9. Use of the multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 8 in the degradation of organic pollutants in seawater under visible light irradiation.
10. Application of the multi-vacancy core-shell ZnO@ZnS heterojunction according to claim 9 in degradation of organic pollutants in seawater under visible light irradiation, characterized in that: The degradation rate of the multi-vacancy core-shell ZnO@ZnS heterojunction in degrading OTC in seawater under visible light irradiation is greater than 50%.
Citation Information
Patent Citations
Preparation method for multilevel structure ZnO@CoS film electrode and application to photoelectric water decomposition thereof
CN106544693A
Method for preparing zinc oxide / zinc sulfide nano heterojunction photocatalyst
CN106622291A
ZnO / ZnS composite material with zinc and oxygen double vacancies as well as preparation method and application of ZnO / ZnS composite material
CN118002152A